Escape plan [videorecording (Blu-Ray + DVD)] - Chapman, Miles; Jesko, Arnell; Schwarzenegger, Arnold; Stallone, Sylvester; Caviezel, Jim, 1968-; Jones, Vinnie, 1965-; Jackson, Curtis, 1975- (Summit Entertainment, 2014)
Ray Breslin, one of the world's foremost authorities on structural security, agrees to take on one last job: breaking out of an ultra-secret, high-tech facility called The Tomb. Deceived and wrongly imprisoned, Ray must recruit fellow inmate Emil Rottmayer to help devise a daring, nearly impossible plan to escape from the most protected and fortified prison ever built.